Exploring Aluminum Alloy Metal Matrix Composites in EDM Using Coupled Factor-level-present Worth Analysis and Fuzzy Analytic Hierarchy Process - Okponyia, K.O.; Oke, S.A. (International Journal of Industrial Engineering and Engineering Management, 2020)
This paper targets two improvement aspects of the electrical discharge machining (EDM) process. First, it formulates the EDM problem as an economic issue incorporating the present worth analysis into the factor-level framework and solves it with the performance analysis flow diagram. Second, it conceptualizes the EDM process as imprecision and uncertainty and solves it with the fuzzy analytical hierarchy process (FAHP) approach. At present, these methods are not accessible to the EDM process engineer to machine the work material, AA6061/10%Al2O3AMMCs. In this study, the EDM process application using these methods on AA6061/10%Al2O3AMMCs is considered. This paper investigates the use of fuzzy AHP multi-criteria and the present worth method to produce a structured approach to model multi-response problem of EDM process parametric optimization concerning composite named AA6061/10%Al2O3AMMCs to obtain a robust design and the best parametric selection. The selected performance measures for the inputs to attain the performance flow analysis using the present worth method are MRR = 17.932 to 31.753 mg/min, TWR = 0.171 to 0.289 mg/min, SR = 8.228 to 12.680 mm and OV = 0.292 to 0.406 mm. The performance flow analysis reveals a present with a value of 1.604 based on the equivalence analysis of the flow diagram's positive and negative sides. The FAHP results showed the enhanced values of 0.1051, 0.2290, and 0.6658 for peak current, pulse on time, and duty factor, respectively. The approach is novel and has not been implemented elsewhere to solve the problem for the combination of materials studied.